Kristine Korlud y Marina Prusac: Iconoclasm from Antiquity to Modernity. - Papoulias, Haris Ch. (THÉMATA. Revista de Filosofía, 2015)
Kristine Korlud y Marina Prusac: Iconoclasm from Antiquity to Modernity.